Kako tehnologija oblikuje medije - Košir, Andrej (Primerjalna književnost, 2017)
This article reviews selected mechanisms by which modern communications technologies shape media. The main thesis is that to a great (if not undue) extent what shapes electronic media are the nature of technological development, functional demands as seen from a technological expert%s point of view, and project administration. Media constitute a complex phenomenon that to a great degree appears to be shaped by technology, and not the reverse. Our hypothesis is that technological progress influenced the understanding or organization of the time, rhythm, and speed with which authors and technology shape information and by which the latter is broadcast in time and space. The roles of authors, editors, media proprietors, and the legal framework have changed, as have related ethical questions. We depict the influence of communications technology on media through the development of leading technological developments over recent decades. We consider the internet, e-books, e-periodicals, social networks, blogs (web diaries), personalizing and contextualizing mechanisms, and use of social signals in web communications. It is not possible here to compile a comprehensive list of advancements. We conclude the paper with a discussion of developments expected in the near future, mainly mechanized social intelligence and its contextual awareness, which will greatly influence the shape of future media.
Keywords: communication technology; communications; digital media; digitalni mediji; innovations; inovacije; komunikacije; komunikacijska tehnologija; mass media; media technologies; medijske tehnologije; množični mediji